The Jacobi elliptic functions and their applications in the advance of mercury's perihelion - Salas S., A.H.; Castillo H., J.E.; Restrepo R., C.E. (Revista Mexicana de Física, 2015)
In this paper we find the exact solution of the nonlinear differential equation describing the trajectory of mercury considering relativisticeffects. Instead of the classical perturbation method we use the Jacobi elliptic functions to obtain the exact solution. The deviation of the perihelion of Mercury and other planets is calculated. The results may be ofgreat interest to astronomers and for those interested in the study of nonlinear differential equations.